Bully for you, Teddy Roosevelt! - Fritz, Jean.; Wimmer, Mike (New York : Scholastic, 1991)
Follows the life of the dynamic twenty-sixth president, discussing his conservation work, hunting expeditions, family life, and political career
Includes bibliographical references (p. 122-123) and index
980
Accelerated Reader AR
Keywords: Roosevelt, Theodore, -- 1858-1919.; Presidents